The roles of receptive and productive language in children's socioemotional development. Issue 4 (30th July 2018) - Rose, Elisabeth; Weinert, Sabine; Ebert, Susanne
Abstract: The purpose of the present study was to investigate the effects of 3‐year‐old children's language comprehension (operationalized by receptive vocabulary and grammar) and language production (operationalized by sentence production and ratings of productive language) on parent‐ and teacher‐rated cooperative behavior, physical aggression, and emotional self‐regulation over a 4‐year period. Analyses were based on a German longitudinal project including 547 typically developing children. Path models showed that receptive but not productive language significantly predicted the development of cooperative behavior when important child and family characteristics (e.g., SES, nonverbal cognitive abilities, and early cooperation at the age of 3) were controlled. In addition, we considered children's gender as a moderator and found compelling gender differences. In boys, only receptive language had an effect on all three aspects of socioemotional development. In girls, only productive language had an effect on the development of aggressive behavior and emotional self‐regulation. This result highlights the relevance of discussing the current results for boys and girls separately.